STUDYING THE PROPERTIES OF HORMONALLY ACTIVE FORMS OF CHOLECALCIFEROL WITH VIKASOLUM DURING EXPERIMENTAL PERIODONTITIS IN RATS - Schnаider S.A.; Suslova, O.V.; Savelieva, N.N.; Anisimov, M.V.; Maslov, A.V.; Noneva, N.O.; Tkachenko, E.K. (World of Medicine and Biology, 2019)
The total of 25 white rats males 1.5-2 - months of age were included in the experiment. Intact group comprised 7 specimens. In the control group, a model of periodontitis was reproduced (7) with administering pelentan per os and replacement of drinking water with 2% EDTA ad libitum. The hormonal forms of vitamin D3 were administered per os in doses per rat a day: 0.1 μg 1.25(OH)2D3 (5 animals) and 1.25 μg 24.25(OH)2D3 (6 animals) together with Vicasolum at a dose of 1.5 mg for 60 days. The hormonal forms of vitamin D3 with Vicasolum showed anti-osteo-resorptive, periodontal protective properties, which resulted in a decrease in the level of periodontal bone resorption, LPO products; activation of antioxidant enzymes; increasing the level of sulfhydryl groups of proteins in the mucous membrane of the oral cavity and the alveolar bone.